Getting hip to vitamin D: A hospitalist project for improving the assessment and treatment of vitamin D deficiency in elderly patients with hip fracture. Issue 11 (5th September 2014) - Stephens, John R.; Williams, Christine; Edwards, Eric; Ossman, Paul; DeWalt, Darren A.
<x xml:space="preserve">Abstract</x> BACKGROUND Vitamin D deficiency is common in elderly patients with hip fracture, and clinical practice guidelines recommend screening this population. Our hospitalist group cares for all patients admitted with hip fracture, yet lacked a standardized approach to screening for and treating vitamin D deficiency in this population. OBJECTIVES To standardize and improve the assessment and treatment of vitamin D deficiency in elderly patients with hip fracture. DESIGN Quality improvement implementation. SETTING Tertiary academic hospital. PATIENTS Adults age >50 years with hip fracture. INTERVENTIONS We implemented a computerized hip fracture order set with preselected orders for 25‐OH vitamin D level and initial supplementation with 1000 IU/day of vitamin D. We presented a review of the literature and performance data to our hospitalist group. MEASUREMENTS Percentage of patients with acute hip fracture screened for vitamin D deficiency and percentage of deficient or insufficient patients discharged on recommended dose of vitamin D (50, 000 IU/wk if level <20 ng/mL). RESULTS The percentage of patients screened for vitamin D deficiency improved from 37.2% (n = 196) before implementation to 93.5% (n = 107) after (P < 0.001). The percentage of deficient or insufficient patients discharged on the recommended vitamin D dose improved from 40.9% to 68.0% (P = 0.008). The prevalence of vitamin D deficiency or insufficiency (25‐OH vitamin D level <30 ng/mL) was 50.0%. CONCLUSIONS Simple interventions, consisting of a change in computerized order set and presentation of evidence and data from group practice, led to significant improvement in the assessment and treatment of vitamin D deficiency in elderly patients with hip fracture. Journal of Hospital Medicine 2014;9:714–719. © 2014 Society of Hospital Medicine